Analysis of the Significance of Keratotopography, Keratopachymetry and Optical Coherence Tomography of the Cornea in the Differential Diagnosis of Pellucid Marginal Corneal Degeneration and Keratoconus - I. V. Vasilieva; S. V. Kostenev; A. V. Vasiliev (Oftalʹmologiâ, 2022)
Purpose. To analyze the significance of keratotopography, keratopachymetry and optical coherence tomography of the cornea in the differential diagnosis of pellucid marginal corneal degeneration with keratoconus.Patients and methods. A retrospective analysis of data from outpatient medical records of 62 patients (62 eyes) with keratectasias and the presence of a crab claw keratotopogram was carried out. Optical coherence tomography of the cornea was performed in all eyes and the parameters of keratopachymetry and corneal elevation were studied on the Pentacam.Results. Optical coherence tomography allowed in all cases to determine the localization of the corneal thinning zone. Only 5 out of 13 indicators of keratopachymetry had statistically significant intergroup differences and can be used in the differential diagnosis of keratectasias.Conclusion. The analysis showed that, in contrast to keratotopography, keratopachymetry and optical coherence tomography of the cornea make it possible to differentiate the type of primary keratectasia.